Salmonella osteomyelitis in a previously healthy neonate: a case report and review of the literature - Canyang Zhan; Jing Du; Lihua Chen (BMC, 2018)
Abstract Background Acute osteomyelitis, which is uncommon in neonates, needs to be quickly diagnosed and treated to avoid devastating sequelae. Therefore, it is important to maintain a high index of suspicion and be aware of the evolving epidemiology and of the emergence of antibiotic resistant and aggressive strains requiring careful monitoring and targeted therapy. The most frequently isolated bacterium in neonates with osteomyelitis is Staphylococcus aureus, while Salmonella is an unusual organism causing osteomyelitis and is exceedingly rare in non-sickle cell disease children. Case presentation We report an extremely rare case of neonatal osteomyelitis caused by Salmonella in a neonate, who was previously healthy. We report this case because it was caused by a rare pathogenic germ in newborns and by its non-specific presentation. Conclusions Salmonella should be kept in mind in the differential diagnosis of neonatal osteomyelitis. It is important to start antibiotic therapy as soon as possible and to adjust therapy in relation to the susceptibility of the bacterial strain.